Trimester Specific Thyroid Profile Reference Ranges for Pregnant Women in South Indian Population - Arokiamary. S,; Kulkarni Sweta, (The Bioscan, 2025)
Introduction: It is crucial to measure thyroid function throughout pregnancy to determine the health of the mother and foetus. However, a woman's thyroid hormone levels alter during pregnancy due to complex physiological changes. If typical reference ranges are not established it becomes challenging to interpret the thyroid profile during pregnancy. The goal of the study was to identify reference levels for thyroid hormone in healthy pregnancy in particular to each trimester. Aim and Objectives: • To study the trimester – specific thyroid profile hormones in pregnant women. • To estimate the level of thyroid hormones ranges in the first, second and third trimester pregnant women. • To establish trimester – specific reference ranges for TSH, free T3 (FT3), and free T4 (FT4) in apparently healthy pregnant women and to compare with standard reference ranges. Methodology: • This study was conducted in a tertiary care hospital at Puducherry with 270 pregnant women • Estimation of thyroid profile using Chemiluminescence immunoassay technique. Result: The normal ranges of thyroid hormone in first, second and third trimesters during normal pregnancy in our study were: total FT3 (2.27-2.79, 2.55-2.82, 2.73- 2.91pg/ml, total FT4 (1.53-2.73, 1.00-1.40, 1.07-1.20ng/dl) and total TSH (1.78-2.32, 2.01-2.56, 2.02-2.46μIU/ml) respectively. Conclusion: The levels of thyroid hormones in pregnancy not only show characteristic changes from non-pregnant state but also vary with each trimester. Hence, trimester specific reference ranges for thyroid hormone need to be defined to ensure correct interpretation of these tests.